Pepducin-mediated G Protein-Coupled Receptor Signaling in the Cardiovascular System - Xu, Heli; Tilley, Douglas G (Journal of cardiovascular pharmacology, 2022)
Pepducins are small-lipidated peptides designed from the intracellular loops of G protein-coupled receptors (GPCRs) that act in an allosteric manner to modulate the activity of GPCRs. Over the past 2 decades, pepducins have progressed initially from pharmacologic tools used to manipulate GPCR activity in an orthosteric site-independent manner to compounds with therapeutic potential that have even been used safely in phase 1 and 2 clinical trials in human subjects. The effect of pepducins at their cognate receptors has been shown to vary between antagonist, partial agonist, and biased agonist outcomes in various primary and clonal cell systems, with even small changes in amino acid sequence altering these properties and their receptor selectivity. To date, pepducins designed from numerous GPCRs have been studied for their impact on pathologic conditions, including cardiovascular diseases such as thrombosis, myocardial infarction, and atherosclerosis. This review will focus in particular on pepducins designed from protease-activated receptors, C-X-C motif chemokine receptors, formyl peptide receptors, and the β2-adrenergic receptor. We will discuss the historic context of pepducin development for each receptor, as well as the structural, signaling, pathophysiologic consequences, and therapeutic potential for each pepducin class.